2014
DOI: 10.1080/17457289.2014.888434
|View full text |Cite
|
Sign up to set email alerts
|

Ballot Structure and Satisfaction with Democracy

Abstract: This paper analyzes the influence of ballot structure over satisfaction with democracy. In line with previous literature, we hypothesize that some ballot structures -such as preferential ballots -generate more satisfaction with democracy than closed ones. Yet, we expect these differences to be especially relevant among the more knowledgeable electorate, since any open ballot structure requires more sophisticated voters. Using CSES surveys, our results do not show a clear and parsimonious relation between ballo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The first study on the topic by Farrell and McAllister (2006) found that levels of satisfaction with democracy tended to be higher in list PR systems allowing voters to cast votes for candidates. Yet, Bosch and Orriols (2014), re-analysing the same dataset, show that satisfaction is only higher in the systems in which the rank ordering of candidates has no impact on which candidates are elected.…”
Section: Voting and Satisfaction With Democracy Under Prmentioning
confidence: 95%
See 1 more Smart Citation
“…The first study on the topic by Farrell and McAllister (2006) found that levels of satisfaction with democracy tended to be higher in list PR systems allowing voters to cast votes for candidates. Yet, Bosch and Orriols (2014), re-analysing the same dataset, show that satisfaction is only higher in the systems in which the rank ordering of candidates has no impact on which candidates are elected.…”
Section: Voting and Satisfaction With Democracy Under Prmentioning
confidence: 95%
“…However, cross-sectional studies find mixed evidence regarding the effect of ballot structure on people's satisfaction with democracy. Levels are often similar in closed-list and flexible-list PR systems (Bosch and Orriols, 2014). However, prior research has only examined aggregate levels of satisfaction with democracy.…”
Section: Introductionmentioning
confidence: 99%
“…That current electoral institutions, as well as some alternative ones if reforms were implemented, are not neutral is a statement that can be easily found in the literature (Benoit, 2000). This is a valid statement concerning the conversion formula as well as regarding the ballot structure (Bosch and Orriols, 2014). This also concerns the impact different electoral rules may exercise upon the formation or not of pre-electoral coalitions (Golder, 2006, Spoon et al 2015, or the influence different rules may exercise on the number of political parties that enter a legislature, to mention but a few areas of research of this literature.…”
Section: Theoretical Background and Quantitative Indexes Employedmentioning
confidence: 93%
“…This modifying effect of the electoral system on the satisfaction gap presented by Anderson and Guillory (1997) has found supportive (e.g., Farrell & McAllister, 2006;Klingemann, 1999), albeit mixed evidence (e.g., Aarts & Thomassen, 2008;Berggren, Fugate, Preuhs, & Still, 2004;McAllister, 2005). The latter studies pointed towards other factors possibly influencing the winnerloser gap, such as economic inequality (Han & Chang, 2016), voters' degree of control over the resulting political representation (Bosch & Orriols, 2014;Pellegata & Memoli, 2018), ideological proximity (Curini et al, 2012;Ezrow & Xezonakis, 2011), the intertemporal dimension of winning (Chang, Chu, & Wu, 2014), strategic voting (Singh, 2014), the availability of direct political participation for losers (Bernauer & Vatter, 2012), and electoral margins (Howell & Justwan, 2013).…”
Section: Satisfaction With Democracy: Review Of Relevant Findingsmentioning
confidence: 97%